Which factors are important for the successful development and implementation of clinical pathways?: a qualitative study - De Allegri, Manuela; Schwarzbach, Matthias; Loerbroks, Adrian; Ronellenfitsch, Ulrich (BMJ Journals, 2011)
Introduction Clinical pathways (CPs) are detailed longitudinal care plans delineating measures to be conducted during a patient's treatment. Although positive effects on resource consumption and quality of care have been shown, CPs are still underutilised in many clinical settings because their development and implementation are difficult. Evidence underpinning successful development and implementation is sparse. - Methods The authors conducted semistructured face-to-face interviews with key staff members involved in the design and implementation of CPs in a large surgery department. Interviewees were asked to provide opinions on various issues, which were previously identified as potentially important in CP development and implementation. The transcribed text was read and coded independently by two researchers. - Results Respondents highlighted the importance of a multidisciplinary participatory approach for CP design and implementation. There was a strong initial fear of losing individual freedom of treatment, which subsided after people worked with CPs in clinical everyday life. It was appreciated that the project originated from people at different levels of the department's hierarchy. Likewise, it was felt that CP implementation granted more autonomy to lower-level staff. - Conclusion The structured qualitative approach of this study provides information on what issues are considered important by staff members for CP design and implementation. Whereas some concepts such as the importance of a multidisciplinary approach or continuous feedback of results are known from theories, others such as strengthening the authority especially of lower-level health professionals through CPs have not been described so far. Many of the findings point towards strong interactions between factors important for CP implementation and a department's organisational structure.